If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(y + -2) + -9 = -7(-2y + 5) + -2y Reorder the terms: 4(-2 + y) + -9 = -7(-2y + 5) + -2y (-2 * 4 + y * 4) + -9 = -7(-2y + 5) + -2y (-8 + 4y) + -9 = -7(-2y + 5) + -2y Reorder the terms: -8 + -9 + 4y = -7(-2y + 5) + -2y Combine like terms: -8 + -9 = -17 -17 + 4y = -7(-2y + 5) + -2y Reorder the terms: -17 + 4y = -7(5 + -2y) + -2y -17 + 4y = (5 * -7 + -2y * -7) + -2y -17 + 4y = (-35 + 14y) + -2y Combine like terms: 14y + -2y = 12y -17 + 4y = -35 + 12y Solving -17 + 4y = -35 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. -17 + 4y + -12y = -35 + 12y + -12y Combine like terms: 4y + -12y = -8y -17 + -8y = -35 + 12y + -12y Combine like terms: 12y + -12y = 0 -17 + -8y = -35 + 0 -17 + -8y = -35 Add '17' to each side of the equation. -17 + 17 + -8y = -35 + 17 Combine like terms: -17 + 17 = 0 0 + -8y = -35 + 17 -8y = -35 + 17 Combine like terms: -35 + 17 = -18 -8y = -18 Divide each side by '-8'. y = 2.25 Simplifying y = 2.25
| 11-w/2=60 | | 4x(5x+7)= | | ax^2+6ax+9a=0 | | -x+15-3x+6=-7x-4x | | (25.12^2)/(4(3.14)) | | -6/7x+17=-61 | | 7/9-5/13 | | (78x-48y)-(68x+28y)= | | -x+5y-3x-2y= | | 4(5y+7z)-28z= | | 5/13+6/11 | | 2(6y+2z)-4z= | | k+-9k-8k-10k=-20 | | 5y(2y-4)+14y= | | 9a-3(a+3)= | | 8c-10c-6=10 | | -1a-24=5a | | 2x+7(8+2x)=8 | | 6(4y+5z)-30z= | | 4log(x-6)=11 | | 16h-13h-2h-1=15 | | (25.12^2)/4(3.14) | | 52=12+4w | | -7/9(x-y+36) | | 2c-c=14 | | (80x-54y)-(62x+9y)= | | 8y-y+2y=18 | | 5(2y+4z)-20z= | | 15+3y=25 | | 4x-5/3x | | 6y(3y-4)+22y= | | (11x+23y)+(38x+50y)= |